Evaluation of Prepectoral Breast Tissue Expander Reconstruction Intraoperative Fill: Air or Saline?. Issue 4 (5th December 2022) - Bamba, Ravinder; Christopher, Laura; Mailey, Brian A.; Mercho, Raphael; Dawson, Steven E.; Hadad, Ivan; Lester, Mary E.; Hassanein, Aladdin H.
Abstract : Summary: Staged implant-based breast reconstruction with immediate tissue expanders (TEs) is the most common method of breast reconstruction after mastectomy. TEs traditionally are filled with saline for expansion. Some surgeons have advocated initial intraoperative fill of the TE with air to avoid excess pressure on ischemic mastectomy skin flaps. The purpose of the study was to compare intraoperative air versus saline tissue fills. All patients who underwent prepectoral TE reconstruction after mastectomy from 2017 to 2019 were reviewed. The primary predictive variable was whether saline or air was used for initial tissue expansion. Outcome variables included mastectomy skin necrosis, nipple necrosis, infection, number of expansions, hematoma, and explantation. A total of 53 patients (88 TEs) were included in the study: 28 patients (44 TEs) who underwent initial intraoperative fill with air and 25 patients (44 TEs) who underwent an initial saline fill were assessed. There were no significant differences in complication rates between initial TE fill with saline versus air, including nipple necrosis, wound dehiscence, cellulitis, abscess, or TE removal ( P = 1.0). The number of postoperative TE fills in the initial air fill group was 3.2 compared to 2.7 in the initial saline fill group ( P = 0.27). Prepectoral TE initial fill with air has similar postoperative outcomes compared to initial saline fill. The authors found no benefit to initially filling prepectoral TEs with air intraoperatively. Given the additional effort of exchanging air for saline during the first postoperative fill, there was no clinical advantage of filling prepectoral TEs with air. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.